Nursing Interventions Through Time : History as Evidence - D'Antonio, Patricia; Lewenson, Sandra (New York : Springer Pub. Co., 2010)
Designated a Doody's Core Title!. "This is a must-read for nurses who are interested in where nursing has been and what nurses have done to get to the present day." Score: 94, 4 stars. --Doody's. Nursing has a rich history that consistently informs contemporary practice and standards. This book, by examining pivotal historical interventions across the spectrum of clinical care, allows nurses of today to incorporate the wisdom of the past into their own daily work. Maternal-child health programs, palliative care, tuberculosis, medications, pediatric care, and diabetes care, and more.
THE SETTING OF BALTIMORE IN THE 1890STHE LUTHERAN DEACONESS NURSE; BALTIMORE DEACONESS SERVICE TO THE COMMUNITY; PARISH DEACONESSES; IMPLICATIONS FOR NURSING PRACTICE TODAY; ACKNOWLEDGMENTS; Section III: NURSING INTERVENTIONS: INFLUENCING CHANGE; Chapter 8: Obstetric Nursing: For the Patient or the Doctor?; INTRODUCTION; RECRUITMENT OF THE NURSE; NURSES AND PHYSICIANS: A USEFUL ALLIANCE; THE PROMISE OF SAFE AND PAINLESS DELIVERIES; OPERATIVE INTERVENTIONS FOR BIRTH; CONFLICT: MANAGING THE SYSTEM AND SUSTAINING THE PATIENT; THE NURSE'S POINT OF VIEW; WHAT TO DO WITH THE EVIDENCE?
Acknowledgments.
Print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Nursing -- History; Evidence-based nursing; Evidence-based nursing -- History; History of Nursing; Evidence-Based Nursing; Soins infirmiers factuels; Soins infirmiers factuels -- Histoire; MEDICAL -- Nursing -- Medical & Surgical; MEDICAL -- Nursing -- Reference; Evidence-based nursing; Nursing; History